Effects of an 8-Week Physical Education Training Program on Physical Fitness in U17–U18 Students - Valiyev, Yusif; Aliyev, Seymur; Tagiyev, Avaz; Huseynova, Kifayet; Hasanov, Turan; Aliyev, Nazim (Physical Education Theory and Methodology, 2026)
Objective. The effectiveness of physical education programs often varies because the specific contribution of exercise sequencing and load progression to fitness outcomes remains insufficiently understood. This study examined how deliberate control of exercise order and progressive load distribution in an 8-week program affects speed, agility, explosive power, and endurance in U17–U18 students. Materials and Methods. Fifty male students aged 17–18 years were randomly assigned to an experimental group (n = 25) and a control group (n = 25). The experimental group completed the structured program three times per week for eight weeks. Physical fitness was assessed using the 30-m sprint, Illinois agility test, standing long jump, and Cooper 12-minute run test. Results. The experimental group showed statistically significant improvements in all four parameters (p < 0.05), with large effect sizes (Cohen’s d = 0.83–1.10), whereas the control group showed no significant changes. Conclusions. The improvements resulted from the sequencing in which speed and agility drills preceded explosive strength exercises, while endurance activities concluded each session, together with progressive load distribution across three microcycles. When this specific order and load progression are followed, substantial gains across multiple fitness components can occur simultaneously. These findings demonstrate that deliberate changes in exercise sequencing and load parameters can influence the magnitude and balance of fitness development, indicating that outcomes are determined by the structured interaction of training components rather than by isolated exercises.